The female-male gap in life expectancy in Poland - Muszyńska, Magdalena M. (Studia Demograficzne, 2011)
The difference in life expectancy between the sexes in Poland started to decline only in 1991, equaling 8.4 years in 2009. In addition, with the rapid increase in male excess mortality between 1989 and 1991, the sex gap also increased. With the exception of excess mortality of male infants, the female advantage in mortality grows with age and reaches the maximum at the age of 65–70 years in 2009. The excess mortality of male infants decreased over the studied years from a contribution of over a year to the sex gap in life expectancy at birth in 1959, to less than a month in 2009. Differences in life expectancy at birth between the sexes in Poland are greater in rural than in urban areas and there is a variation between the voivodships: from 7.9 years in 2008 in the Pomorskie voivodship to 10.2 years in Lubelskie. The largest variation in the sex gap in life expectancy was that between different educational groups: and the gap decreased with the level of educational attainment. Diseases of the circulatory system are a major group of causes of death, with the highest contribution to the sex gap in life expectancy, and were the largest factor in the narrowing of the sex gap between 1991 and 2006. External causes of death were the second-largest group contributing to the sex gap in life expectancy at birth in 1991, and to the narrowing of the gap in the studied period. Over the years under study, the importance of malignant neoplasms for the phenomenon in consideration increased, but at the same time life expectancy of both sexes rose due to improvements in mortality from this group of causes. According to our estimates, smoking- and alcohol-related causes of death together explained about 50% of the total difference in life expectancy at birth between the sexes in the years 1989–2006. In this period, the sex gap in life expectancy due to these causes of death increased, which is opposite to what was reported for other developed countries.